Protective Effect of SIRT1 Activator on the Knee With Osteoarthritis - Zhou, Zhenquan; Deng, Zhenhan; Liu, Yuwei; Zheng, Yizi; Yang, Shiwei; Lu, Wei; Xiao, Deming; Zhu, Weimin (Frontiers in Physiology, 2021)
Osteoarthritis (OA), one of the most common chronic musculoskeletal disorders, is deemed to be correlated with aging. The SIRT1 activator, resveratrol, acts as a crucial regulator of aging and may have a potential therapeutic effect on OA. Rabbit OA models were established through destabilized medial meniscus surgery. A total of 40 healthy male New Zealand rabbits were divided into five groups: control group (sham operation), OA group, as well as low dose (LD), middle dose (MD), and high dose (HD) resveratrol-treated OA groups. 6 weeks after operation, 0.8 ml of normal saline was injected into the knee joints every other day in the control and OA groups, and 0.8 ml of 5, 10, and 15 μmol/L resveratrol was injected into the knee joints every other day in the LD, MD, and HD group, respectively. The rabbits were sacrificed 2 weeks after medication, and the articular cartilage of the knee joint was collected for Micro-CT, histology and Western blot analysis. Obvious articular cartilage lesion and joint space narrowing were detected in the OA group. Compared with the OA group, less osteoarthritic changes were observed in the MD and HD groups. The MD and HD groups had significantly lower bone volume fraction, trabecular number and Mankin scores than the LD and OA groups (p < 0.05). No significant difference was found between the OA and LD groups (p > 0.05). The expressions of SIRT1 and p53 detected by western blot were consistent with the aforementioned findings. Therefore, resveratrol can activate the SIRT1 gene to play a protective role in the OA process by inhibiting chondrocyte apoptosis, trabecular bone number increasing of the subchondral bone, as well as elevation of bone density. It demonstrated the importance of SIRT1 in maintaining articular cartilage health and provided a promising therapeutic intervention in the treatment of OA.